2021
DOI: 10.3390/ijms22136773
|View full text |Cite
|
Sign up to set email alerts
|

Restriction of Manganese Intake Prevents the Onset of Brain Manganese Overload in Zip14−/− Mice

Abstract: As a newly identified manganese transport protein, ZIP14 is highly expressed in the small intestine and liver, which are the two principal organs involved in regulating systemic manganese homeostasis. Loss of ZIP14 function leads to manganese overload in both humans and mice. Excess manganese in the body primarily affects the central nervous system, resulting in irreversible neurological disorders. Therefore, to prevent the onset of brain manganese accumulation becomes critical. In this study, we used Zip14−/−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 33 publications
2
11
0
Order By: Relevance
“…The age-associated differences in murine manganese metabolism were previously reported, showing that 3-week-old mice appeared to have higher liver manganese concentrations than 12-week-old mice [ 31 ]. Our results have shown that hepatic ZIP8 is downregulated in mice exposed to high manganese during the neonatal period (in 3-week-old mice), but not in mice receiving a high-manganese diet after reaching maturity.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The age-associated differences in murine manganese metabolism were previously reported, showing that 3-week-old mice appeared to have higher liver manganese concentrations than 12-week-old mice [ 31 ]. Our results have shown that hepatic ZIP8 is downregulated in mice exposed to high manganese during the neonatal period (in 3-week-old mice), but not in mice receiving a high-manganese diet after reaching maturity.…”
Section: Resultsmentioning
confidence: 96%
“…We developed our neonatal manganese overload model by feeding breeder mice a purified diet containing 20 ppm (control) or 2000 ppm (high) of manganese throughout mating, gestation, and lactation. Our previous study determined that the manganese content in the maternal milk from mice on the high-manganese diet was about 3 times that from mice on the control diet [ 31 ]. Given that this dietary intervention led to an alteration in breast milk manganese content, the pups experienced differences in manganese intake before weaning.…”
Section: Resultsmentioning
confidence: 99%
“…However, the extent of manganese accumulation caused by the loss of intestinal ZIP14 was not as severe as that observed in Zip14 −/− mice because it has been reported that the blood manganese levels in Zip14 −/− mice of a similar age were about 15 times as high as the wild-type (WT) littermates [ 28 ]. We hypothesize that since hepatic ZIP14 was intact in Zip14 -In-KO mice, excess manganese resulting from the loss of intestinal ZIP14 could be partially removed through hepatobiliary excretion, leading to less severe manganese loading in Zip14 -In-KO mice.…”
Section: Resultsmentioning
confidence: 99%
“…ZIP14 inactivation primarily impairs the central nervous system and leads to neurodegenerative symptoms due to manganese hyperaccumulation in the brain. For example, the brain manganese in 6-to-12-week-old Zip14 −/− mice was reported to be about 10 times as high as that in WT mice [ 28 ]. In the present study, we examined the effect of tissue-specific Zip14 deletion on brain manganese in 9-week-old mice and found that Zip14 -L-KO mice had normal brain manganese while Zip14 -In-KO mice developed increased brain manganese loading (increased by 40% in male mice and by 20% in female mice) when compared with the Zip14 flox/flox control mice ( Figure 6 A,B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation